2014
DOI: 10.1089/cbr.2013.1599
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Receptor Radionuclide Therapy in Patients with Inoperable Meningiomas: Our Experience and Review of the Literature

Abstract: In consideration of its efficacy and the lack of significant toxicity, PRRT of meningiomas using (111)In-Pentetreotide could be proposed even nowadays when the use of (177)Lu- or (90)Y-labeled peptides seems unsafe, namely in patients with renal impairment/toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…Our study as well as other recent work (3,4) suggests that somatostatin receptor-targeted radiopeptides represent a promising therapeutic option for patients with progressive meningiomas. Herein lies an opportunity for the field of nuclear medicine, in collaboration with neurooncology, radiation oncology, and neurosurgery, to translate this tool from a promising option into a validated therapy.…”
Section: Replysupporting
confidence: 74%
“…Our study as well as other recent work (3,4) suggests that somatostatin receptor-targeted radiopeptides represent a promising therapeutic option for patients with progressive meningiomas. Herein lies an opportunity for the field of nuclear medicine, in collaboration with neurooncology, radiation oncology, and neurosurgery, to translate this tool from a promising option into a validated therapy.…”
Section: Replysupporting
confidence: 74%
“…Moreover, the results of a phase II prospective clinical trial, in which 67.6% of patients achieved SD and the mean survival of all enrolled patients was 8.6 years, lent further support to the use of SSTR2-directed PRRT in patients with progressive unresectable meningioma (102). Many more clinical studies have confirmed the efficacy and safety of SSTR2-targeted PRRT in the treatment of meningiomas (103)(104)(105). Indeed, the recent European Association of Neuro-Oncology guidelines on meningioma have declared PRRT a promising approach to treat refractory meningiomas across all WHO grades in the future (1).…”
Section: Ptsmentioning
confidence: 84%
“…However, patients with impaired renal function have to be evaluated thoroughly before considering therapy with radiolabeled somatostatin analogs. Alternatively, according to the results of Minutoli et al (22), 111 In-labeled somatostatin analogs might be used instead of b-emitting radionuclides in cases with a higher risk of renal toxicity.…”
Section: Discussionmentioning
confidence: 99%